2018
DOI: 10.1080/2162402x.2018.1438105
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral vectors transduce alveolar macrophages in lung cancer models

Abstract: Adenoviral vectors expressing Cre recombinase are commonly used to initiate tumor formation in murine lung cancer models. While these vectors are designed to target genetic recombination to lung epithelial cells, adenoviruses can infect additional cell types that potentially influence tumor development. Our goal was to explore the consequences of adenoviral-mediated alveolar macrophage (AM) transduction in a Kras-initiated lung tumor model. As expected, treatment of animals harboring the KrasLSL-G12D allele an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Importantly, the slower growth of these tumors allows the microenvironment to develop over time, which more closely resembles the long-term tumor residency of macrophages in human tumors. Previous viral-Cre–induced lung cancer models have documented transduction of lung-resident AMs and consequently modification of conditional allele by Cre recombinase in AMs ( Tippimanchai et al, 2018 ). Thus, we developed a novel model that specifically induces tdTomato protein expression and oncogenic alterations in neoplastic cells to enable tracking of phagocytic activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the slower growth of these tumors allows the microenvironment to develop over time, which more closely resembles the long-term tumor residency of macrophages in human tumors. Previous viral-Cre–induced lung cancer models have documented transduction of lung-resident AMs and consequently modification of conditional allele by Cre recombinase in AMs ( Tippimanchai et al, 2018 ). Thus, we developed a novel model that specifically induces tdTomato protein expression and oncogenic alterations in neoplastic cells to enable tracking of phagocytic activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Wu R. S. et al (2015) found that DEX could enhance the phagocytic activity of macrophages in mice with endotoxemia. Tippimanchai et al (2018) suggested that DEX could reduce the number of alveolar macrophages and inhibit their phagocytosis in septic mice. García et al (2003) suggest that α 2 -AR controls phagocytosis and chemotaxis in primary cultured rat peritoneal macrophages, maintaining phagocytosis at optimal levels.…”
Section: Dex's Regulatory Effect On Immune Cells and Inflammationmentioning
confidence: 99%
“…Beyond these two important effects, mutation induction in bystander cells may also substantially influence epithelial cell response. For instance, one study found when using Ad5-Cre to induce oncogenic Kras that 70% of the recombined cells were alveolar macrophages that exhibited a phenotype and persisted in the lungs for up to 6 months, thus significantly altering the immune environment (Tippimanchai et al 2018). While the coadministration of immunosuppressive medications and use of cell type-specific promoters may mitigate some of these concerns, it should be noted that promoter element-driven constructs may not faithfully recapitulate the endogenous levels and patterns of gene expression in vivo since they lack long-range regulatory elements (Schoenfelder & Fraser 2019).…”
Section: Using Viruses To Infer Cancer Cells Of Originmentioning
confidence: 99%